2023
DOI: 10.3390/nu15071790
|View full text |Cite
|
Sign up to set email alerts
|

Phase Angle, Handgrip Strength, and Other Indicators of Nutritional Status in Cancer Patients Undergoing Different Nutritional Strategies: A Systematic Review and Meta-Analysis

Abstract: Malnutrition in cancer patients is one of the most influential factors in the evolution and mortality of such patients. To reduce the incidence of malnutrition, it is necessary to establish a correct nutritional intervention. For this purpose, precise tools and indicators must be developed to determine the patient’s condition. The main objective of this systematic review and meta-analysis was to analyze the relationship between different nutritional strategies, phase angle (PA), and handgrip strength in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Additionally, systematic reviews and meta-analyses have shown that nutritional interventions for patients with cancer can change their phase angles. 41 ) These findings suggest that rehabilitation, including resistance training, nutritional management, or their combination, may have a greater potential to improve the phase angle. Therefore, to maximize improvement of patient outcomes, careful observation of the phase angle and its trends, rather than routine and conventional treatment, may help facilitate high-quality treatment, including personalized nutrition and exercise, in a multidisciplinary manner.…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, systematic reviews and meta-analyses have shown that nutritional interventions for patients with cancer can change their phase angles. 41 ) These findings suggest that rehabilitation, including resistance training, nutritional management, or their combination, may have a greater potential to improve the phase angle. Therefore, to maximize improvement of patient outcomes, careful observation of the phase angle and its trends, rather than routine and conventional treatment, may help facilitate high-quality treatment, including personalized nutrition and exercise, in a multidisciplinary manner.…”
Section: Discussionmentioning
confidence: 91%
“…The ESPEN Guidelines on Nutrition in Geriatrics also state that restrictive diets are not recommended for overweight older adults [ 37 ]. A meta-analysis suggested that nutritional interventions in patients with cancer could increase their PhA values [ 38 ]. We suggest that preventing a shortage of carbohydrates and ensuring a sufficient intake of total calories may contribute to an increased PhA and promote healthy aging among healthy older males.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant tumors are one of the leading causes of death worldwide. [29] Scientists are seeking new effective methods of treatment in oncology. Research is being conducted to search for substances that may aid in the fight against cancerous diseases.…”
Section: Creatine Supplementation In Cancer Therapy -Its Potential Ap...mentioning
confidence: 99%
“…Proper nutritional intervention is crucial for improving therapeutic outcomes and quality of life. [29] [31] Currently, there is no established effective treatment regimen for cancer-related cachexia, which necessitates the need to find new methods of treatment. Creatine helps strengthen muscles and improve strength, which is why it has potential applications in the treatment of cancer-related cachexia.…”
Section: Impact On Muscle Function Body Mass and Cancer Cachexiamentioning
confidence: 99%
See 1 more Smart Citation